Phenomenon of Demikhov. In the Vishnevsky Institute of Surgery (1947–1955): Development mammaro coronary anastomosis (1952–1953). Organ transplantation in the light of the Michurin theory (1953) - S. P. Glyantsev (Трансплантология (Москва), 2016)
.